PENINGKATAN HASIL BELAJAR SAINS DENGAN MENERAPKAN PENDEKATAN BELAJAR KONTEKSTUAL - WATINI, SRI (PPs UNJ, 2011)
The purpose of the research is to apply the contextual learning approach, in the frame of increasing of sains learning result optimally. Popultion in this research is the children of TK Bani Taqwa Bekasi implemented on October up to December 2009 with the total numbers 21(twenty) children. Method implemented is action research consisting of severel step, they are as follows: planning step, implementing step, observing step and reflextion step. During the implementating for three circles. Reserch result is showing us that there is increasing of sains learning. Result with the procentage for circle I domain cognitive 43,3%, afective 46,6%, phycomotoric 56,6%, circle II cognitive 56,6%, afective 59,1%, phycomotoric 66,3% and circle III cognitive 79%, afective 83,7%, phycomotoric 80,9%.Keywords: sains learning, contextual learning